Germany : - Reinhardt, Kurt F. (Frederick Ungar Publishing Co., 1950)
This book is a brilliant survey, both political and cultural, of Germany's history from the time of the pagan tribes to the collapse of the Weimar Republic. Dr. Reinhardt sees Germany as an integral part of European tradition, to which she has contributed immeasurably and from which she departs only to court disaster. Each section of the book opens with a chronological table, followed by a brief account of political events and a discussion of major cultural trends. Literature, art, music, religion, trade, fashions and manners are treated with scholary detail, in a polished and readable style which provides penetrating insight into the truc background of modern Germany.